Enhanced thermoelectric power factor of tensile drawn poly(3-hexylthiophene) - Hynynen, Jonna; Järsvall, Emmy; Kroon, Renee; Zhang, Yadong; Barlow, Stephen; Marder, Seth R.; Kemerink, Martijn; Lund, Anja; Müller, Christian (ACS Macro Letters, 2019)
The thermoelectric power factor of a broad range of organic semiconductors scales with their electrical conductivity according to a widely obeyed power law, and therefore, strategies that permit this empirical trend to be surpassed are highly sought after. Here, tensile drawing of the conjugated polymer poly(3-hexylthiophene) (P3HT) is employed to create free-standing films with a high degree of uniaxial alignment. Along the direction of orientation, sequential doping with a molybdenum tris(dithiolene) complex leads to a 5-fold enhancement of the power factor beyond the predicted value, reaching up to 16 μW m-1 K-2 for a conductivity of about 13 S cm-1. Neither stretching nor doping affect the glass transition temperature of P3HT, giving rise to robust free-standing materials that are of interest for the design of flexible thermoelectric devices.